Tremisses y potentes en el nordeste de Lusitania (siglos vi-vii) - Iñaki Martín Viso (Mélanges de la Casa de Velázquez)
This article examines the places where isolated gold coins have been found from the Suevic and Visigothic eras in the north-eastern part of Lusitania. The study reveals a pattern of heterogeneous power centres (civitates, high places, churches) where there is evidence of the presence of local aristocracies who possessed coin. These potentes were linked to the regnum through their part in the management and organisation of taxation, as the tremis was an official coin and as such could be used as a symbol of social prestige.